2019
DOI: 10.1097/txd.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Peripheral Blood CD19-Positive Rate and Antibody-Mediated Rejection Following Rituximab Administration in Kidney Transplant Recipients

Abstract: Background. Rituximab is used widely for desensitization in ABO-incompatible and donor-specific antibody-positive kidney transplantation. However, data about the effects of individual differences in rituximab-induced B-cell suppression on antibody-mediated rejection (AMR) remain unknown. We aimed to assess the association between CD19-positive rate and AMR following rituximab administration after kidney transplantation. Methods. Overall, 42 patients who underwent rituxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Subsequently, a total of 75 papers were excluded during either full‐text screening or data extraction. Ultimately, 82 citations 2,6–86 including 65,386 participants met inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a total of 75 papers were excluded during either full‐text screening or data extraction. Ultimately, 82 citations 2,6–86 including 65,386 participants met inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 studies reported neutropenia incidence 2 , 6,11,14,15,26,30,31,34,36,39,42,44,46–48,51,60,63,64,68,69,75,76,78,81,85 . The absolute neutrophil count (ANC) threshold to define neutropenia varied widely; the majority of the studies ( n = 12) reported neutropenia with a threshold of ANC <1000/μl 2,6,11,15,26,36,44,51,63,75,81,85 followed by a threshold of <500/μl ( n = 8 11,26,34,42,44,60,81,85 ), <1500/μl ( n = 7 26,44,46,60,68,76,81 ), and <2000/μl ( n = 3 64,78,81 ); in 7 studies 14,30,39,42,47,48,69 , a threshold definition was not reported. In 1 study, 31 neutropenia was defined using an International Classification of Diseases, Ninth Revision (ICD‐9) code.…”
Section: Resultsmentioning
confidence: 99%